Prevalence of Bladder and Bowel Dysfunction in Toilet-Trained Children With Urinary Tract Infection and/or Primary Vesicoureteral Reflux: A Systematic Review and Meta-Analysis - Jitendra Meena; Georgie Mathew; Pankaj Hari; Aditi Sinha; Arvind Bagga (Frontiers Media S.A., 2020)
Introduction: Urinary tract infection (UTI) in children leads to renal scarring in 10-15% of patients. Urinary tract anomalies and bladder and bowel dysfunction (BBD) are documented risk factors for recurrent UTIs. Estimates of baseline prevalence of BBD in children with UTI will help the clinician in the management strategy. Hence, a systematic review and meta-analysis was conducted to estimate the pooled prevalence of BBD.Methods: MEDLINE, EMBASE, and CENTRAL (Cochrane Central Register of Controlled Trials) databases were searched for articles related to UTI, primary vesicoureteral reflux (VUR), and BBD. We included studies that provided prevalence of BBD in toilet-trained patients aged 1-18 years with UTI and/or VUR. BBD was defined based on clinical history or questionnaire or urodynamic studies. Two authors independently reviewed, assessed, and abstracted data from studies. Pooled prevalence was calculated based on a random effects model.Results: Forty-three studies fulfilling the eligibility criteria were selected from a total of 1,731 studies. Among patients presenting with UTI without primary VUR, pooled prevalence of BBD was 41% (95% CI: 26-55; nine studies, 920 patients, I2 = 96.0%), whereas its prevalence in patients with primary VUR was 49% (43-56; 30 studies, 5,060 patients, I2 = 96.0%). Weighting by the study design and quality did not affect the prevalence. In patients with primary VUR, prevalence of BBD was higher in females (53%; 42-65) than in males (44%; 15-73). In studies where urodynamic study was used for the diagnosis of BBD, prevalence was 63%. The presence of BBD in patients with primary VUR increased risk of recurrent UTIs [relative risk (RR): 2.1; 1.7-2.5]. In five studies that reported separate data on constipation, pooled prevalence of constipation was 27% (16-37).Conclusion: Almost half of the patients with primary VUR have BBD, and its presence increases the risk of recurrent UTIs. Trends of high BBD prevalence were also observed in patients presenting with UTI without VUR. These prevalence estimates suggest that all toilet-trained children presenting with UTI with or without VUR should be assessed for BBD, which will help in their further management.